Coding by voice in a projectional editor - Cancelinha, Alexandre Filipe Magalhães (2023)
The increase in software production is associated with a significant rise in occupational illnesses, such as Repetitive Strain Injury (RSI), which stems from the excessive repetition of movements in parts of the body such as the shoulders, elbows, wrists and hands. These conditions can have a negative impact on the productivity of programmers, who depend on these parts to carry out essential tasks. In order to address this problem, efforts have been made to find a solution that replaces the use of the keyboard and mouse with voice commands. In this context, Jasay was conceived with the aim of combining the idea of a structured editor with the integration of voice commands in two parts. The first part involves capturing and transcribing voice commands into text, while the second consists of processing these commands in order to make changes to the Java source code. In order to assess the effectiveness of this prototype, two tests were carried out. The first test involved the participation of users, whose results were positive, managing to complete the tasks in a reasonable time using Jasay. The second test compared the execution time of some tasks between Jasay and using the keyboard and mouse. Although the keyboard-mouse combination performed slightly better, the difference can be considered acceptable. This project represents an innovative approach in the search for solutions aimed at improving the health and productivity of programmers by reducing dependence on repetitive movements and introducing a viable alternative based on voice commands.